A construção da imagem do converso: Castela e Aragão (séculos XIV-XV) - Follador, Kellen Jacobsen (2009)
This dissertation aims to understand the creation of the image of the anointed, i.e. the one converted Christian, based on the point of view of the old-Christian ones in Castile and Aragon in the XIV and XV centuries. During all the Middle Age Jews had been considered oathbreakers and an unfaithful people, whom beyond were guilty for Deicide brought also several diseases to the Christians. All the anti-Judaism that existed among Christians has been made into political myths that represented the imaginary of the Christianity in relation to Jews. For many times this anti-Judaism arose and the Jewish communities were pursued and attacked, as in the Castile and Aragon kingdoms in the end of 14th century. In 1391, the attacks that had devastated the Jewish communities from both kingdoms had provoked the conversion of many Jews to the Christianity because they were obliged to choose between baptism or death. This contingent of neophytes started to be recognized as the converted ones or new Christians showing that it had a discrimination between the new Christians of Jewish ancestry and those that had been born in the Christianity, considered the ones of pure ancestry. This difference among these two Christians groups increased with the time, since the old Christians distrusted in the converted religious faith. The religious question caused conflicts that were combined to economic, social and political questions. All of these questions were joined to that imaginary and its political myths that had motivated the popular revolts against the converted, specifically the revolt in 1449, in the city of Toledo. The old Christians believed that the anointed planned to destroy them because they caused many troubles both politically, socially and economically, and also because they were considered false Christians. In this context the Sententia Statute come up and stipulated that all Jewish ancestry Christians would be considered indign to possess some positions and benefits in the city. This document brought to existence the Pureness of Blood Statutes that deprived the Christians descendant of Jews of many “honor” positions, which could not be occupied by one who was an “impure blood”. Considering this context, we believe that such differentiation based on the ancestry appeared because the old Christians saw the converted people as Jews, not as real Christians. The consequence of that was the prohibition of the converted ones to have access to specific positions and social status that belonged exclusively to the old Christians since the great period of conversions, in 1391.